Multiple electrode aggregometry and vasodilator stimulated phosphoprotein-phosphorylation assay in clinical routine for prediction of postprocedural major adverse cardiovascular events - Freynhofer, Matthias K; Brozovic, Ivan; Bruno, Veronika; Farhan, Serdar; Vogel, Birgit; Jakl, Gabriele; Willheim, Martin; Hübl, Wolfgang; Wojta, Johann; Huber, Kurt (Thrombosis and haemostasis, 2011)
Reduced antiplatelet effect of clopidogrel assessed with multiple electrode aggregometry (MEA) and vasodilator stimulated phosphoprotein-phosphorylation (VASP-P) assay has been proven to predict major adverse cardiovascular events (MACE) after coronary stenting. So far no consecutive registry has evaluated the usefulness of different adenosine diphosphate-based platelet function tests to predict outcome in unselected patients. Hence, our objective was to determine the feasibility of MEA and VASP-P for clinical routine and whether low-response to clopidogrel as determined by MEA and/or the VASP-P assays predicts MACE in a "real-life" population undergoing coronary stenting. Three-hundred consecutive patients were included in this prospective registry. Blood was sampled 6-24 hours after stenting to measure MEA and VASP-P. The use of glycoprotein-IIb/IIIa-blockers limited MEA to 196 measurements. Concerning the VASP-P assay, 300 measurements were achieved. Receiver Operating Characteristics (ROC)-curves of sensitivity and specificity estimates for MACE were plotted for VASP-P assay. The area under the ROC-curve was 0.683 (p=0.014) for the platelet reactivity index (PRI) calculated from median fluorescence intensities (FI) with an optimal cut-off at 60.2% PRI. Patients above 60.2% had a significantly increased risk for MACE at six months follow-up (p=0.007). Estimating the cut-offs for the PRI from mean FI (52%) or from geometric mean FI (56.6%) led to clinically relevant differences. VASP-P assay is feasible for clinical routine to measure clopidogrel effects and to predict post-procedural MACE in unselected patients. With regard to differing cut-offs, exact standardisation of the VASP-P assay is mandatory. The use of GP-IIb/IIIa-blockers prevents MEA testing and limits its usability in unselected patients.